Students Perception on Digital Storytelling in Speaking - Fadilla, Julia Nur; Nugraha, Agung; Lestari, Yosa Dwi; Darsih, Endang (UM Purwokerto Press, 2025)
This study aims to investigate the implementation and impact of digital storytelling in improving students' speaking skills in an English as a Foreign Language (EFL) class. As speaking remains one of the most challenging language skills for EFL students, various creative teaching strategies have been developed to address these challenges, one of which is digital storytelling. The research was conducted as a case study involving students of the English Study Program at Kuningan University. Through qualitative descriptive methods, data were collected using observations, interviews, and documentation. The results indicate that the digital storytelling process involves several stages: scriptwriting, voice recording, collecting supporting media, and video editing, with lecturers acting as facilitators. The implementation of this technique proved effective in enhancing students' confidence, fluency, pronunciation, and vocabulary. Additionally, it fostered students’ creativity, motivation, and independent learning attitudes. The study also highlights some obstacles, such as students’ limited video editing skills and the time-consuming nature of the process. Nevertheless, the findings support previous research that digital storytelling offers an engaging, interactive, and adaptable learning environment, making it a valuable tool in EFL classrooms to improve speaking ability. Therefore, it is recommended that this method be integrated regularly into speaking courses with proper technical guidance provided for students.